Particle deposition and fluid flow characteristics in turbulent corrugated pipe flow using Eulerian-Lagrangian approach - Md Nazmus Sakib; Md. Shahneoug Shuvo; Rezwana Rahman; Sumon Saha (Heliyon, 2023)
A numerical simulation of aerosol particle deposition in a horizontal circular pipe with a corrugated wall under turbulent flow has been carried out in this research. This paper uses the RNG k-ε turbulence model with Enhanced Wall Treatment to simulate fluid flow. Furthermore, the Lagrangian particle tracking model simulates particle deposition in the corrugated pipe. Air-particle interaction is influenced by Stokes number, surface roughness, flow velocity, particle diameter, and pipe diameter. For the parametric simulation, particle diameter varies from 1 to 30 μm, whereas the Reynolds number ranges from 5000 to 10,000. The effect of corrugation height and pipe diameter on deposition efficiency is also investigated. This study shows that corrugation height significantly increases particle deposition compared to the smooth wall pipe. As the pipe diameter decreases, keeping the corrugation ratio constant, deposition efficiency also increases. Moreover, high flow velocity enhances deposition efficiency for particle diameters lower than 5 μm.